A Comparative Study of Dropout Rates and Causes for Two Different Distance Education Courses - Pierrakeas, Christos; Xenos, Michalis; Panagiotakopoulos, Christos; Vergidis, Dimitris (International Review of Research in Open and Distributed Learning, 2004)
This paper reports the results of a survey conducted to examine the root causes leading to student dropout at a Greek distance education university. Data was gathered from two different courses – an undergraduate course leading to a Bachelors degree in Informatics (characterized by high dropout rates), and a postgraduate course leading to a Masters degree in education (characterized by low dropout rates). A comparative analysis of these two different courses revealed important similarities in dropout percentages and the reasons cited by students for dropping out. Our analysis also revealed important differences as well. This paper presents the results of a survey designed to investigate the relationship between dropout with intrinsic (student-related) factors such as sickness, work/ school conflict etc., and extrinsic (institutional-related) factors such as study methods and materials, educational approach, and tutor influence.